Pengaruh Substitusi Silase Rumput Kume dengan Fodder Jagung Hidroponik Terhadap Konsumsi dan Kecernaan Karbohidrat, Konsentrasi Vollatile Fatty Acid dan Kadar Glukosa Darah Kambing Kacang Jantan - Devi Puay; Gustaf Oematan; Daud Amalo; Imanuel Benu (Animal Agricultura, 2023)
This aim of this research is to determine the effect of substitution of sorghum plumosum silage with hydroponic corn fodder on carbohydrate intake and digestibility, VFA concentration and blood glucose levels of male kacang goats. This study used 3 male goats under one year of age and body weight between 13,5-17,1 kg. The research method used latin square design with 3 periods and 3 treatments, consisting of FCG0: 70% kume grass silage + 30% concentrate, FCG1: 35% kume grass silage + 35% corn fodder + 30% concentrate, FCG2: 20% kume grass silage + 50% corn fodder + 30% concentrate. The parameters analyzed were carbohydrate intake, carbohydrate digestibility, VFA concentration and blood glucose levels. The result as follows that: then means carbohydrates consumption (g/h/d) FCG0: 245,99069±161,85, FCG1: 185,55441±61,14, FCG2: 260,90534±70,35. Carbohydrates digestibility (%) FCG0: 60,17990±16,93, FCG1: 66,39760±4,04, FCG2: 82,29166±5,45. VFA concentration (mM) FCG0: 101,386±34,25, FCG1: 124,043±17,85, FCG2: 98,778±14,80. Blood glucose levels (mg/dl) FCG0: 59,66333±4,46, FCG1: 59,80667±13,59, FCG2: 62,86667±3,16. The analysis results showed that the treatments had no significant effect (P>0,05) on carbohydrate intake and digestibility, VFA concentration and blood glucose levels. The conclusion of this study is that feed 20% of sorghum plumosum silage with 50% of hydroponic corn fodder give the same response with 70% of sorghum plumosum silage of male kacang goats.